Lived Experience of a Permanent Rupture Between Mother and Daughter - Germaine, Helen (European Journal for Qualitative Research in Psychotherapy, 2011)
This research explores the lived experience of the rupture in the relationship between Jenny (a pseud- onym) - an 18 year old, pregnant, unmarried, young woman in Britain in 1968 - and her mother. In a relational-centred research interview, Jenny shares her experience proceeding the rupture, the narrative point of the rupture itself and the occurring experience of her relationship after the rupture. Phenom- enological analysis reveals Jenny’s experience is one of shame and guilt in relation to her mother. She feels exposed, humiliated and ‘at fault.’ Jenny misses a shared sense of pride with her mother and in- stead experiences rejection not only of herself, but also through the new life she has created. She devel- ops a number of ways to protect herself from her own painful internal experience. Notably she protects her mother from criticism by taking responsibility for her mother’s feelings and behaviours. Yet there is a sense of a desperate internal confusion of experience as Jenny continually returns the question of the ‘why’ of her mother’s behaviour. The pain of rejection and isolation is felt deeply by Jenny within the relationship rupture with her mother. She feels her own deep sadness and loss as interwoven into her mother’s.